Effect of coil positioning and orientation of the quadruple butterfly coil during transcranial magnetic stimulation - Oluwaponmile Faith Afuwape; Priyam Rastogi; David Jiles; Life Fellow IEEE (AIP Advances, 2021)
Transcranial Magnetic Stimulation (TMS) is a non-invasive neuromodulation technique for treating neurological and psychiatric disorders. It is a proven technique that is safe and considered very effective when compared to conventional brain surgery or drug therapy. Researchers and clinicians are interested in understanding the distribution of the induced electric field (E-Field) during TMS and determining its effectiveness in treating neurological disorders. TMS studies are primarily focused on enhancing the focality and depth of penetration of the induced electric field in order to increase its effectiveness. Coil orientation has been confirmed to have an effect on the magnitude and direction of the induced E-Field. In this paper, we study the effect of the orientation of the novel Quadruple Butterfly Coil (QBC) on the distribution of the induced E-Field. Finite element analyses were conducted with the orientation of the QBC in steps of 15° over the vertex of two head models and about the transverse (XY –) plane and coronal (XZ –) plane of the head model. The maximum electric field intensity (E-Max) and stimulated volume of the brain (V-Half) were computed and compared to determine the optimal coil orientation.